Impact of imagery-enhanced interpretation training on offline and online interpretations in worry. (January 2020) - Feng, Ya-Chun; Krahé, Charlotte; Meeten, Frances; Sumich, Alexander; Mok, C.L. Michelle; Hirsch, Colette R.
Abstract: Worry and rumination are forms of repetitive negative thinking (RNT) that are maintained by negative interpretations and a predominance of abstract, verbal thinking. Hence, facilitating more positive interpretations and imagery-based thinking in combination may reduce RNT. Study 1 administered interpretation training with and without enhanced imagery, and an active control condition (designed not to change interpretations), in individuals with high levels of RNT (worry and/or rumination). Combining interpretation training with sustained imagery resulted in the highest levels of positive interpretation bias using an offline test of interpretation bias (when individuals have time to reflect). Study 2 investigated whether imagery-enhanced interpretation training influences online interpretations when ambiguous information is first encountered, indexed by reaction times and amplitude of the N400 event-related potential, as well as enhances offline positive interpretations in high worriers. It also examined whether imagery-enhanced interpretation training reduces negative thought intrusions associated with worry. Both online (reaction time) and offline interpretations were more positive following imagery-enhanced interpretation training, and negative thoughts were reduced, compared to the active control. However, no differences emerged on neurophysiological markers during the online task. Hence, brief interpretation training encompassing sustained imagery modifies online and offline interpretations, but further training may be required to impact upon neurophysiological measures. Highlights: People who worry or ruminate a lot make negative interpretations and think verbally. Positive interpretation training with and without enhanced imagery was compared. Imagery-enhanced training promoted the most positive interpretations. It promoted positive online, as well as offline, interpretations in high worriers. It also reduced negative thoughts compared to an active control.